The Forgotten Azores Current: A Long-Term Perspective - Frazão, Helena C.; Prien, Ralf D.; Schulz-Bull, Detlef E.; Seidov, Dan; Waniek, Joanna J. (Frontiers in Marine Science, 2022)
The Atlantic Meridional Overturning Circulation (AMOC) and its surface limb, the Gulf Stream, are in their weakest state since the last millennium. The consequences of this weakening in the Northeast Atlantic are not yet known. We show that the slowdown of the Gulf Stream in the 1960s, 1970s, and after 2000 may have caused a delayed weakening of the Azores Current. Concurrently, the Azores Front associated with the Azores Current migrated northward since the 1970s due to gradual changes in the Atlantic Multidecadal Oscillation and ocean heat content. We argue that the AMOC slowdown is also detectable in the low-energy region of the Northeast Atlantic and that the dynamics of Azores Current tightly connects to that of the dynamics of the Gulf Stream and AMOC on decadal and longer time scales.